(untitled) (Malaysian Journal of Learning and Instruction, 2014)
Purpose – The study aimed to explore, describe and analyse the design and implementation of clinical simulation as a pedagogical tool in bridging the deficiency of higher order thinking skills among para-medical students, and to make recommendations on incorporating clinical simulation as a pedagogical tool to enhance thinking skills and align the curriculum. Methodology – A qualitative approach using interpretativedescriptive case study design was utilized in framing the researchstudy. Purposive sampling was used to select 20 final year paramedicalstudents and five teaching staff who participated in thisstudy. Data was collected through direct and participant observation,interviews and document analysis. Thematic analysis using Stake’sCountenance Model was utilized to analyse and present the findings. Findings – On the basis of these analyses, the study supports that (i) clinical simulation facilitates the infusion of higher order thinking skills; (ii) clinical simulation that uses thinking pedagogy nurtures the development of higher order thinking skills; and (iii) clinical simulation uses higher order thinking modality to promote, understand and transfer learning. While facilitators play a crucial role in engaging learners with higher order thinking modality and make students’ thinking visible by utilizing the use of metacognition and self-regulation abilities, learners become more autonomous, strategic and motivated to apply effort and strategies in a variety of meaningful contexts. Significance – The findings of this study can assist curriculum managers, college administrators and educators regarding the inclusion of clinical simulation as an instructional approach to enhance higher order thinking skills among para-medical students.